2018
DOI: 10.1073/pnas.1714401115
|View full text |Cite
|
Sign up to set email alerts
|

Slow domain reconfiguration causes power-law kinetics in a two-state enzyme

Abstract: Protein dynamics are typically captured well by rate equations that predict exponential decays for two-state reactions. Here, we describe a remarkable exception. The electron-transfer enzyme quiescin sulfhydryl oxidase (QSOX), a natural fusion of two functionally distinct domains, switches between open- and closed-domain arrangements with apparent power-law kinetics. Using single-molecule FRET experiments on time scales from nanoseconds to milliseconds, we show that the unusual open-close kinetics results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…While these structures suggest models with well‐defined states, our results sketch DtpA as an ensemble of multiple conformers with rapid dynamics. Recent studies showed that enzymes obey structural dynamics much faster than the timescales required for turnover . Such dynamics are also prevalent in DtpA, irrespective of the lipid environment (Figure C,D and Figure C).…”
Section: Resultsmentioning
confidence: 87%
“…While these structures suggest models with well‐defined states, our results sketch DtpA as an ensemble of multiple conformers with rapid dynamics. Recent studies showed that enzymes obey structural dynamics much faster than the timescales required for turnover . Such dynamics are also prevalent in DtpA, irrespective of the lipid environment (Figure C,D and Figure C).…”
Section: Resultsmentioning
confidence: 87%
“…Another interesting parallel was described very recently in the two-domain enzyme quiescin sulfhydryl oxidase from the parasite Trypanosoma brucei 37 . Here the two domains are joined by a short disordered linker, and the enzyme transitions between open and closed states in the course of the catalytic cycle.…”
Section: Discussionmentioning
confidence: 78%
“…Here the two domains are joined by a short disordered linker, and the enzyme transitions between open and closed states in the course of the catalytic cycle. Fuzzy and apparently non-specific interactions between the two domains, arising as a result of their high mutual effective concentration, give rise to a rugged energy landscape, sub-diffusive conformational dynamics and ultimately to unusual, non-exponential reaction kinetics in this enzyme 37 . Thus, non-specific interactions, occurring as a result of the high effective concentration ensured by tethering with a disordered linker, can modulate protein function in a range of ways.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity is expected to be static at the fast nanosecond time-scale of the donor fluorescence lifetime 65 , which is expected to cause deviations from the predicted linear dependence between donor lifetime and transfer efficiency 65,66 . This deviation is indeed observed experimentally ( Fig S17).…”
Section: Conformations Of Dtpa In Sapnpsmentioning
confidence: 99%
“…Numerous bacterial POT structures have been determined to date [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] . We focus on the E. coli peptide transporter DtpA 59,60 to explore the effect of different environments such as detergents and Saposin nanoparticles 61,62 (SapNPs) with different lipid compositions on the conformation of the protein using single molecule FRET (smFRET) [63][64][65][66][67][68] . DtpA is an ideal model system since its substrate specificity is remarkably similar to that of its homologs PepT1 and PepT2 from human 36,[69][70][71][72][73][74][75] .…”
Section: Introductionmentioning
confidence: 99%